Service-learning instructional design considerations - Maddrell, Jennifer (Journal of computing in higher education, 2014)
This paper explores the design of service - learning experiences to engage college students in the real-world application of course subject matter. Service learning is an educational approach that combines community service, academic coursework, and work-based applied learning. Based on data gathered during a series of recent interviews conducted with students, faculty, and instructional designers with applied and service-learning experience, a set of design considerations is offered for the facilitation of service-learning experiences in both campus-based and online courses.